«Cold War 2.0» and neo-kennanite approach to Russia: Siberia and Russian Nation - A. V. Sushko (Омский научный вестник: Серия "Общество. История. Современность")
The article contains the analytical commentary on Russian translation of the separate chapter from the book «Long Telegram 2: Neo-Kennanite Approach to Russia» by American anthropologist, historian and political scientist Peter Eltsov. It analyzes critically the reasons, according to Peter Eltsov, why in the historical perspective the collapse of Russia is possible